Forearm Pronation Osteotomy for Supination Contracture Secondary to Obstetrical Brachial Plexus Palsy: A Retrospective Cohort Study. Issue 6 (September 2017) - Gladstein, Aharon Z.; Sachleben, Brant; Ho, Emily S.; Anthony, Alison; Clarke, Howard M.; Hopyan, Sevan
Abstract : Background: Obstetrical brachial plexus palsy can lead to fixed forearm supination contracture. Fixed supination may lead to functional deficits as the affected hand cannot be positioned optimally for activities on a desk such as writing and typing, or for using tools including utensils, which require a neutral or pronated forearm. Forearm pronation osteotomy has been used to address this problem, although the functional benefit over nonoperative management has not been clearly defined. Potentially deleterious consequences on hand function that requires supination or fine motor skills are also uncertain. Methods: Patients with fixed forearm supination contracture were selected from our institutional brachial plexus database. Those who underwent both bone forearm rotational osteotomy were analyzed for age at time of surgery, preoperative forearm resting position, active and passive supination and pronation, and preoperative function assessed by the brachial plexus outcome measure (BPOM) and active movement scale (AMS). Preoperative results were compared with values obtained at follow-up at least 12 months postoperatively. A matched cohort of children with fixed forearm supination contracture that were treated nonoperatively and followed for at least 12 months, was also selected. For this group, forearm resting position, movement, AMS, and BPOM scores were analyzed at a baseline clinic visit and the most recent follow-up. Changes in forearm resting position, AMS, and BPOM activity scale scores were then compared between groups. Results: Records were obtained for 14 cases and 10 controls. Study groups were similar with respect to resting forearm position, hand function, and time from initial to final evaluation. Groups differed with respect to age and active supination. We observed a statistically significant change in resting position among operative patients compared with their preoperative status and compared with controls. Hand-specific AMS score did not change significantly in the operative group as compared with controls. The BPOM score for drums, reflective of function in neutral rotation to mild pronation, improved in the operated patients as compared with controls. There was no loss of plate holding ability (reflective of supination function, putty (grasp), or bead placement (fine motor) among the operated patients as compared with controls. Conclusions: By pronating resting forearm position by about 90 degrees to near neutral, osteotomy resulted in improved neutral to mild pronation-dependent function without loss of supination-dependent function or hand motor skills. Level of Evidence: Level III—retrospective cohort study.